Steigerwald, The Sixties And The End Of Modern America` - Nass, David (Teaching History: A Journal of Methods, 1996)
David Steigerwald is assistant professor of history at The Ohio State University at Marion. He has written a number of articles for scholarly journals and has a forthcoming monograph, Wilsonian Liberals and the Passing of the Universal Ideal.